Development of three-dimensional prints of arthritic joints for supporting patients' awareness to structural damage - Kleyer, Arnd; Beyer, Laura; Simon, Christoph; Stemmler, Fabian; Englbrecht, Matthias; Beyer, Christian; Rech, Juergen; Manger, Bernhard; Krönke, Gerhard; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2017)
Rheumatoid arthritis (RA) and psoriatic arthritis (PsA) result in severe joint destruction and functional disability if left untreated. We aim to develop tools that help patients with RA and PsA to understand and experience the impact of inflammatory joint disease on the integrity of their (juxta-articular) bone and increase adherence to medical treatment. In this study, we used high-resolution peripheral quantitative computed tomography (HR-pQCT) to develop 3D prototypes of patients' finger joints.HR-pQCT (XtremeCT, Scanco) measurements were performed in healthy individuals and patients with inflammatory joint disease, followed by a 3D print using the objet30 printer. Healthy participants (n = 10), and patients (n = 15 with RA and 15 with PsA) underwent a detailed, standardized interview with demonstration of printed joints.Utilizing HR-pQCT images of metacarpophalangeal (MCP) heads, high quality and exact 3D prints as prototypes were created. Erosions in different sizes and the trabecular network printed in detail were visualized, demonstrating structural reduction in arthritic vs. healthy bone. After demonstration of 3D prints (healthy vs. erosive joint, visual and haptic) 26/39 (66%) participants (including healthy volunteers) were deeply affected, often quoting "shock". Of the patients with RA and PsA, 13/15 (86%) and 11/15 (73%), respectively, stated that they would rethink their attitude to medication adherence. More importantly, 21/24 patients with RA or PsA (87.5%) expressed that they would have wished to see such 3D prints during their first disease-specific conversations.Using arthro-haptic 3D printed prototypes of joints may help to better understand the impact of inflammatory arthritides on bone integrity and long-term damage.
EVALuna2:13404